2003
DOI: 10.1038/ng1169
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3ε is important for neuronal migration by binding to NUDEL: a molecular explanation for Miller–Dieker syndrome

Abstract: Heterozygous deletions of 17p13.3 result in the human neuronal migration disorders isolated lissencephaly sequence (ILS) and the more severe Miller-Dieker syndrome (MDS). Mutations in PAFAH1B1 (the gene encoding LIS1) are responsible for ILS and contribute to MDS, but the genetic causes of the greater severity of MDS are unknown. Here, we show that the gene encoding 14-3-3epsilon (YWHAE), one of a family of ubiquitous phosphoserine/threonine-binding proteins, is always deleted in individuals with MDS. Mice def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
352
0
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 378 publications
(368 citation statements)
references
References 47 publications
11
352
0
5
Order By: Relevance
“…185 14-3-3e thus complexes with LIS1 and NDEL1 in vivo and is responsible for maintaining their correct localization. Following their demonstration that DISC1 associates with 14-3-3e, Taya et al 88 demonstrated that many proteins were present in the DISC1 affinity column eluate in addition to KIF5B and 14-3-3e, including LIS1 and NDEL1.…”
Section: Lis1 Ndel1 Nde1 and Disc1mentioning
confidence: 99%
“…185 14-3-3e thus complexes with LIS1 and NDEL1 in vivo and is responsible for maintaining their correct localization. Following their demonstration that DISC1 associates with 14-3-3e, Taya et al 88 demonstrated that many proteins were present in the DISC1 affinity column eluate in addition to KIF5B and 14-3-3e, including LIS1 and NDEL1.…”
Section: Lis1 Ndel1 Nde1 and Disc1mentioning
confidence: 99%
“…The specific elimination of certain 14-3-3 isoforms by genetic means or association of their deletion with distinct syndromes also supports the notion that isoform-specific functions and interactions exist. For example, deletion of 14-3-3ε is found in patients with Miller-Dieker Syndrome and results in a neuronal migration disorder [19]. In Drosophila melanogaster 14-3-3ε is required for correct timing of mitosis in undisturbed post-blastoderm cell cycles, whereas 14-3-3ζ is required for normal chromosomal segregation during syncytial mitosis [20].…”
Section: Introductionmentioning
confidence: 99%
“…This is of particular interest as loss of a single member of this family (14-3-3⑀) leads to abnormalities in neuronal migration during brain development in mice (4) and is tightly linked to the severity of lissencephalies resulting from genetic loss of Pafah1b1 (the gene encoding Lis1) in humans (4). A query of our dataset for phosphorylation sites creating these two modes of 14-3-3 binding identified 10 phosphopeptides (Fig.…”
Section: Large-scale Phosphorylation Site Analysis Of the Developing mentioning
confidence: 99%
“…The profound influence of protein phosphorylation on mammalian brain development has strong genetic support. This is exemplified by the important brain phenotypes observed in mice with loss of function mutations in genes encoding kinases such as p35/cyclin-dependent kinase 5 (Cdk5) 1 (1, 2), loss of tyrosine phosphorylation sites in signaling molecules such as the Reelin-stimulated adaptor protein Disabled-1 (3), or loss of genes encoding proteins that interact with phosphorylated protein motifs such as 14-3-3⑀ (4).…”
mentioning
confidence: 99%